Wave energy conversion (Elsevier ocean engineering book series, 2003)
Wave energy, together with other renewable energy resources is expected to provide a small but significant proportion of future energy requirements without adding to pollution and global warming. This practical and concise reference considers alternative application methods, explains the concepts behind wave energy conversion and investigates wave power activities across the globe. Explores the potential of using the power generated by waves as a natural energy resource Considers the power transfer systems needed to do this, and looks at the environmental impacts